Design and Prototype of an Industrial Monitoring and Protection System. - Nabusha, Alice (Kabale University, 2024)
This project presents the design and prototyping of an Industrial Monitoring and Protection System aimed at ensuring the safety and operational efficiency of industrial environments. The system integrates multiple sensors to monitor critical parameters, including ambient light levels, temperature, and smoke detection, ensuring rapid response to potential hazards. A Light Dependent Resistor (LDR) monitors light levels, triggering a GSM module to send alert messages when excessive lighting is detected. A temperature sensor continuously measures ambient temperature, and in the event of overheating, the GSM module is activated to notify operators. Additionally, a smoke sensor provides early detection of potential fire outbreaks by sending a similar GSM-triggered alert. A relay switch automatically disconnects any connected load when any of the monitored conditions breach safety thresholds, preventing damage to equipment and personnel. The system's status is displayed on an OLED screen, showing real-time readings from all sensors, and offering operators a comprehensive view of the monitored environment. The proposed system enhances industrial safety, providing real-time monitoring, automated protection mechanisms, and early warning capabilities. The implementation of this system highlights the potential of affordable and scalable solutions for improving industrial safety, ensuring immediate response to hazardous conditions, and minimizing downtime.